Community Factors In Efforts To Advance Rural Tourism - Ahmad Mansur (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Tourism has an attraction for everyone, both tourism practitioners and tourism enthusiasts. This study examines community factors in an effort to help develop rural tourism in the Mount Sumbing area, specifically in Mangli village. The objectives are 1) What are the main factors for the community to develop village tourism? 2) What is the community's motivation for developing village tourism. 3) What is the role of the community in efforts to develop village tourism? 4) What are the community's efforts in developing village tourism. This research method is a qualitative phenomenological approach with key community factors in tourist villages. The results of the discussion in this research are 1) the main factor for the community in developing village tourism is of course because it can increase the turnover of the mangle economy and reduce unemployment in the community, especially village youth. 2) the community's motivation for developing a tourist village, namely making Mangli village known to everyone, both locally, nationally and internationally. 3) the role of the Mangli tourist village community is to work together to prepare several tourist attractions that maximize their potential, namely the very beautiful natural scenery because it is the highest village in the Mount Sumbing area. Make something new every 6 months by modifying tourist attractions with a slightly different concept and creating rural tourism packages. 4) Community efforts in developing tourist villages, namely by collaborating in tourism village promotion efforts with the Magelang district government and content creators, and receiving training on hospitality training in an effort to improve human resources (HR) for Mangli village tourism managers.